Consumer testing of the preliminary paediatric food- based dietary guidelines, among English- and Afrikaans-speaking mothers, for healthy children aged 1 – 7 years in the city of Cape Town, South Africa - Scott, Lesley Dalene (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MNutr (Human Nutrition))--University of Stellenbosch, 2006.